Penerapan Algoritma ID3 dalam Prediksi Kebutuhan Pupuk - Milyani Aritonang (Journal of Information System Research (JOSH), 2021)
The need for fertilizer at the Plant Protection Development Unit (UPPT) is uncertain depending on the demand of farmers, therefore it is necessary to predict fertilizer needs. There are five types of fertilizers predicted by the Plant Protection Development Unit (UPPT), including Urea fertilizer, ZA fertilizer, SP-36 fertilizer, NPK fertilizer, and Organic fertilizer, so fertilizer needs can be predicted. In predicting data mining on fertilizer needs using the ID3 algorithm. Where it works is calculating the value of entropy and gain to get the final result in the form of a tree to the decision and rule. Testing is done using the tanagra software. The results of the tests carried out on the tanagra application using the ID3 algorithm are in the form of a decision tree, while in the calculation the results obtained are in the form of a decision tree.